Dying for Victorian Medicine - Hurren, E. author. aut Link
XVIII, 398 p.
Keywords: The first book to provide a detailed analysis of the body-trafficking networks of the dead poor that underpinned the expansion of medical education from Victorian times. With an even-handed approach to the business of anatomy, Hurren uses remarkable case histories which still echo a vibrant body-business on the internet today in a biomedical age.